2020
DOI: 10.1534/genetics.119.303013
|View full text |Cite
|
Sign up to set email alerts
|

A Microbe Associated with Sleep Revealed by a Novel Systems Genetic Analysis of the Microbiome in Collaborative Cross Mice

Abstract: The microbiome influences health and disease through complex networks of host genetics, genomics, microbes, and environment. Identifying the mechanisms of these interactions has remained challenging. Systems genetics in laboratory mice (Mus musculus) enables data-driven discovery of biological network components and mechanisms of host–microbial interactions underlying disease phenotypes. To examine the interplay among the whole host genome, transcriptome, and microbiome, we mapped QTL and correlated the abunda… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 55 publications
3
30
0
Order By: Relevance
“…model, we identified a range of microbial profiles associated with specific genotypes, suggesting that PWD alleles at specific loci modulate gut microbiome composition. This notion is supported by previous studies demonstrating a strong divergence between gut microbiomes of B6 and PWK/PhJ mice (a close relative of the PWD strain) (80), and strong genetic effects on the microbiome composition in Collaborative Cross mice, which carry B6 and PWK/PhJ alleles (81). Nonetheless, our experiments were not designed to exclude potential founder/strain isolation effects on the microbiome that can be prevalent in mouse studies (82,83), and we cannot rule out a contribution of such effects to the observed microbiome diversity of our consomic strains.…”
Section: Discussionsupporting
confidence: 76%
“…model, we identified a range of microbial profiles associated with specific genotypes, suggesting that PWD alleles at specific loci modulate gut microbiome composition. This notion is supported by previous studies demonstrating a strong divergence between gut microbiomes of B6 and PWK/PhJ mice (a close relative of the PWD strain) (80), and strong genetic effects on the microbiome composition in Collaborative Cross mice, which carry B6 and PWK/PhJ alleles (81). Nonetheless, our experiments were not designed to exclude potential founder/strain isolation effects on the microbiome that can be prevalent in mouse studies (82,83), and we cannot rule out a contribution of such effects to the observed microbiome diversity of our consomic strains.…”
Section: Discussionsupporting
confidence: 76%
“…Comprehensive gene mapping studies of behavioral, physiological, circadian, and molecular phenotypes, as well as microbial abundance, conducted in a genetically diverse Collaborative Cross (CC; see Table 1 for a detailed description) mouse colony (Bubier et al, 2020), reported 41 disease-related behavioral and physiological phenotypes associated with microbial abundance and with sleep phenotypes. Over half of them ( 22) included differential abundance of Odoribacter spp.…”
Section: Alterations In Sleep-wake Cyclesmentioning
confidence: 99%
“…This resource has been used to identify novel candidate genes and variants associated with drug-induced adverse effects (32,33), responses to pollutants (34), and respiratory innate immunity (35)(36)(37). Additionally, the CC has been used to study transcriptional correlates of disease features (38)(39)(40). Thus, this population is appropriate for understanding genetic contributions to complex disease phenotypes and dissecting causal mechanisms of O3 toxicity.…”
Section: Introductionmentioning
confidence: 99%